Design of poly(HEMA) particles in supercritical carbon dioxide for protein delivery - Parilti, Rahmet (2018)
A vast majority of the polymer nanocarriers have been designed and developed for the controlled and targeted release of hydrophobic drugs. However, there are still some challenges to design appropriate carriers for the delivery of therapeutic proteins or peptides. Although the history of the protein/peptide based drugs dates back to insulin production, they have taken great attention since the last decades due to their possible broad range of therapeutic applications. They might offer more specific and safer therapies in comparison to small molecules drugs. Nonetheless, their encapsulation remains challenging especially to preserve their specific structure and activity in the formulations. For this purpose, hydrogel particles (nano-/microgels) have emerged as promising polymer carriers for such proteins.